041 A systematic video analysis of the mechanism of injury of achilles tendon ruptures. (3rd March 2020) - O'Neill, Seth; Gibson, Nichola; Regan, Dawn; Walton, Katriona
Abstract : Background: There is currently limited evidence identifying the mechanism of Achilles tendon rupture (ATR). Identification of this mechanism would aid rehabilitation and injury prevention strategies. Objective: Determine the movement pattern (mechanism of injury) for ATRs. Design: A systematic video search was completed of all publicly available videos capturing ATR. Identified videos were then analysed in slow motion by three blinded reviewers. Setting: Subjects of any athletic level participating in sporting events where included. Patients (or Participants): Any subject suffering a verifiable ATR captured on video. Ruptures were verified either by self-report or media release in the case of athletes. A total of 495, 120 eligible videos where identified, with 57 separate ATR events being retained for data analysis. Interventions (or assessment of risk factors): An initial review was used to develop an understanding of important variables. These included Ankle, knee, Hip and trunk movements, Plantar flexor muscle activity (eccentric/concentric), contact/non-contact, sporting activity, age, gender and where possible activity duration prior to rupture. Main outcome measurements: Identification of the mechanism (description of the movement pattern associated) ATR. Results: A total of 57 subjects with confirmed ATR were identified. Various sports were associated with ATR's, field sports accounted for 27 whilst other sports accounted for 30. High load eccentric activity of the plantarflexor muscles was identified as occurring in all injuries. This was associated with dorsiflexion of the ankle and concurrent knee extension in 100% of subjects. Hip extension was only identified in 86% of subjects and 91% of ATR's were non-contact. Conclusions: The injury mechanism for Achilles tendon rupture involves dorsiflexion of the foot with knee extension, whilst the plantarflexor muscles are eccentrically contracting. Further research is required to determine if the addition of a similar movement/motor control task would improve rehabilitation or serve as an injury prevention strategy.